Real-world pathogen spectrum, clinical actionability, and host correlates of first-time mNGS testing in hospitalized patients with hematologic diseases - Ziyi Li; ZiHui Dong; LeMin Jiao; YuDie Cai; YangMiao Zhang; HaiTing Wei; TianQi Fang; ZiYang Zhang; Hang Liu (Frontiers in Cellular and Infection Microbiology, 2026)
Background Patients with hematologic diseases are highly susceptible to infection. Conventional tests often have low sensitivity. Metagenomic next-generation sequencing (mNGS) can detect many pathogens at once, but its clinical value depends on how the results are interpreted. It is often hard to tell true infection from colonization or contamination. Methods We retrospectively studied hospitalized hematologic patients Only adult patients (≥18 years) who received mNGS for the first time. Detected organisms were reclassified using a clinical actionability system. We also analyzed the relationships between mNGS findings, host characteristics, and short-term outcomes. Results A total of 134 patients were included. At least one organism was detected in 87.3% of patients, but only 58.2% had highly actionable results. Bacteria were the most common findings, followed by viruses and fungi. Mixed detections were frequent. Actionable results were seen more often in respiratory specimens than in blood specimens. Viral detection was associated with immune status. Pathogen read counts were only weakly related to inflammatory markers and did not independently predict adverse outcomes. Age was the only independent risk factor for adverse outcome. Conclusion mNGS had a high detection rate in hematologic patients, but not all positive findings were clinically important. Result interpretation should take specimen type and host status into account. Pathogen read counts alone were not useful for predicting short-term outcome.